Effect of non-thermal hurdles in shelf life enhancement of sugarcane juice. (September 2019) - Kohli, Gautam; Jain, Gaurav; Bisht, Akshay; Upadhyay, Ashutosh; Kumar, Anit; Dabir, Shardul
Abstract: In this work, sugarcane juice was preserved using non-thermal hurdles consisting of microfluidisation and natural polypeptides (nisin and polylysine). The effects were compared with thermal hurdles which comprised of pasteurization and Potassium Metabisulfite (KMS) and the untreated control sample. All the samples were stored in glass bottles at 5±2 °C and evaluated for physico-chemical, microbial and sensory parameters till 63 days. In the untreated sample, pH and total soluble solids (TSS) decreased, whereas, titrable acidity and color (L* and a*) values increased significantly (P  ≤  0.01). Both thermal and non-thermal hurdles were able to cause a complete reduction in polyphenoloxidase activity which was 23 units in the control sample. In the sample treated with thermal hurdles small changes in pH, TSS, titrable acidity, color (L* and a*) occurred during storage. On the contrary, the physico-chemical properties of juice samples treated with non-thermal hurdles were stable throughout the storage period and were more acceptable to the sensory panel than the pasteurized sample. Using non-thermal hurdles, 100% reduction in initial microbial load of 3.19 × 10 6  CFU/ml was achieved and remained within 50 CFU/ml ensuring the shelf life of 56 days. Graphical abstract: Image 1 Highlights: Preservation of sugarcane juice was achieved using hurdle technology approach. The shelf life of 56 days was obtained at refrigerated conditions for the sugarcane juice. Juice preserved using hurdle approach was highly accepted by the sensory panel.